Diamond McConnells' Taping Technique versus Counterforce Elbow Orthosis in the Treatment of Lateral Epicondylitis: a Randomized Controlled Trial - Ibrahim Dewir (Rehabilitacja Medyczna, 2021)
Introduction: Lateral epicondylitis, commonly referred to as tennis elbow, is one of the most common lesions of the arm. There are many treatment options available for tennis elbow; taping techniques and splints are commonly used.